Polynomials and General Degree-Based Topological Indices of Generalized Sierpinski Networks. (9th February 2021) - Fan, Chengmei; Munir, M. Mobeen; Hussain, Zafar; Athar, Muhammad; Liu, Jia-Bao
Abstract : Sierpinski networks are networks of fractal nature having several applications in computer science, music, chemistry, and mathematics. These networks are commonly used in chaos, fractals, recursive sequences, and complex systems. In this article, we compute various connectivity polynomials such as M -polynomial, Zagreb polynomials, and forgotten polynomial of generalized Sierpinski networks S k n and recover some well-known degree-based topological indices from these. We also compute the most general Zagreb index known as α, β -Zagreb index and several other general indices of similar nature for this network. Our results are the natural generalizations of already available results for particular classes of such type of networks.